2021
DOI: 10.1002/pro.4228
|View full text |Cite
|
Sign up to set email alerts
|

New covalent bonding ability for proteins

Abstract: To expand protein's covalent bonding ability, latent bioreactive unnatural amino acids have been designed and genetically encoded into proteins, which react with specific natural amino acid residues through proximity‐enabled bioreactivity. The resultant new covalent bonds can be selectively created within and between proteins in vitro, in cells, and in vivo. Offering diverse properties previously unattainable, these covalent linkages have been harnessed to enhance protein properties, to modulate protein functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Our results demonstrate that nanobodies can be readily engineered into covalent binders through incorporating a latent bioreactive Uaa, which reacts with a natural residue of the target protein only upon nanobody-target binding, expanding the scope of PERx that we previously developed and applied to the immune-checkpoint PD-1/PD-L1. 19 20 Sites in nanobody appropriate for FSY or FFY incorporation and cross-linking were identified either by inspecting the structure of nanobody-target complex 44 or simply screening all sites in nanobody’s three CDRs. Recent breakthrough in accurate prediction of protein structure and interactions have made structural information available for a broad range of proteins, 45 46 which will greatly facilitate structure-guided site identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that nanobodies can be readily engineered into covalent binders through incorporating a latent bioreactive Uaa, which reacts with a natural residue of the target protein only upon nanobody-target binding, expanding the scope of PERx that we previously developed and applied to the immune-checkpoint PD-1/PD-L1. 19 20 Sites in nanobody appropriate for FSY or FFY incorporation and cross-linking were identified either by inspecting the structure of nanobody-target complex 44 or simply screening all sites in nanobody’s three CDRs. Recent breakthrough in accurate prediction of protein structure and interactions have made structural information available for a broad range of proteins, 45 46 which will greatly facilitate structure-guided site identification.…”
Section: Discussionmentioning
confidence: 99%
“…18 To break this natural barrier, we recently reported a Proximity-Enabled Reactive therapeutics (PERx) strategy to generate covalent protein drugs. 19 20 A latent bioreactive unnatural amino acid (Uaa) is incorporated into the protein drug through genetic code expansion, 21 which reacts with a natural residue on the target only upon drug-target binding, realizing specific cross-linking of the drug to the target covalently. We have demonstrated that a covalent PD-1 drug efficiently inhibits tumor growth in mice, with therapeutic efficacy superior to that of an FDA-approved antibody.…”
Section: Introductionmentioning
confidence: 99%
“…Moving beyond characterizations, leveraging the high throughput capabilities of yeast display with libraries of ncAA-containing proteins is expected to enable the discovery and evolution of synthetic proteins with an expanded chemical repertoire. Established yeast display magnetic selections and fluorescence-activated cell sorting strategies can be combined with libraries encoding ncAAs bearing various reactive groups 35,36,38,39,43,44,68,85,102,103 or with ncAAs that facilitate conjugations with chemical warheads. 35,38,41,42,68,85,96,102 This powerful combination provides a wide range of opportunities for covalent antibody discovery.…”
Section: P a G E 23 | 31mentioning
confidence: 99%
“…Established yeast display magnetic selections and fluorescence-activated cell sorting strategies can be combined with libraries encoding ncAAs bearing various reactive groups 35,36,38,39,43,44,68,85,102,103 or with ncAAs that facilitate conjugations with chemical warheads. 35,38,41,42,68,85,96,102 This powerful combination provides a wide range of opportunities for covalent antibody discovery. Our results show that the phenotype resulting from ncAA-mediated covalent bond formation can be assayed on the yeast surface, while prior work in yeast display format established high throughput screens to tune the efficiency and selectivity of covalent bond formation.…”
Section: P a G E 23 | 31mentioning
confidence: 99%
“…Adding new covalent bonding capability to proteins would offer diverse properties unattainable with natural proteins, and would enable novel avenues for researching and engineering proteins. 1 Latent bioreactive unnatural amino acids (Uaas) have been designed and site-specifically incorporated into proteins through genetic code expansion. [2][3][4][5] These latent bioreactive Uaas react with natural amino acid residues through proximityenabled reactivity, generating covalent linkages within or between proteins specifically, which have been harnessed to enhance protein properties, to probe protein interactions, and to develop covalent protein drugs.…”
mentioning
confidence: 99%